Trinocular Calibration Method Based on Binocular Calibration - XU Zhen-Ying; LI Wen-Bin; WANG Yun; LUO Chun; GAO Shu-Yuan; CAO Dan-Dan (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In order to solve the self-occlusion problem in plane-based multi-camera calibration system and expand the measurement range, a tri-camera vision system based on binocular calibration is proposed. The three cameras are grouped into two pairs, while the public camera is taken as the reference to build the global coordinate. By calibration of the measured absolute distance and the true absolute distance, global calibration is realized. The MRE (mean relative error) of the global calibration of the two camera pairs in the experiments can be as low as 0.277% and 0.328% respectively. Experiment results show that this method is feasible, simple and effective, and has high precision. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1417